Bacteriorhodopsin and its Mutants allude a breakthrough impending to artificial retina construction and strategies for curing blindness - Saeedi, Pardis; Mohammadian Moosaabadi, Jafar; Behmanesh, Mehrdad; Eidi, Akram; Fallah Mehrabadi, Jalil (Archives of Advances in Biosciences, 2011)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Bacteriorhodopsin, a model system in nanobiotechnology, is a light-sensitive protein found in the archaean Halobacterium salinarum and a very identical protein to visual Rhodopsin. The modification of biological function of BR and its versatile properties is valuable for technical applications including the artificial retina. These photoactive elements of native and particular mutants of bacteriorhodopsin make protein films, used in artificial retinal implants, to treat some retinal diseases and disorders. The two major reasons of retinal photoreceptor cell deterioration are Age-related Macular Degeneration (AMD) and Retinitis Pigmentosa (RP). As in vitro culture of Halobacterium is very difficult, and isolation procedure is much time consuming and usually inefficient, so genetic construction of protein is essential. Here, we have produced two types of bacteriorhodopsin, a native and a mutant BR (D85E) and studied their opto-electric responses with respect to wavelength and absorption properties. They are prerequisite for designing artificial retina (sensors) based on biomolecules. Therefore, the new promising technology soon will conceivably eradicate the blindness.